The Emotional Intelligence (E.I.) and “Perrotta Human Emotions - Questionnaire - 1” (PHE-Q-1): Development, regulation and validation of a new psychometric instrument - Perrotta, Giulio; Basiletti, Vanessa (Archives of Community Medicine and Public Health, 2023)
Background: Based on the Perrotta Human Emotions Model (PHEM-2), a psychometric tool was modelled that could help the therapist gain a deep understanding of the patient's emotional capacity, and thus his emotional intelligence, also concerning follow-up and achievements during the psychotherapeutic course. Aim: To check whether the PHEM-2 can be structured into a psychometric tool that assesses the subject's emotional intelligence to calibrate the most appropriate psychotherapeutic intervention for the specific case. Methods: Clinical interview, based on narrative-anamnestic and documentary evidence, and battery of psychometric tests. Results: The PHE-Q-1 demonstrated its clinical usefulness during psychotherapy sessions to improve the patient's emotional capacity and confirmed its validity relative to statistical comparison, reporting an R = 0.999 and p ≤ 0.001. Conclusion: The validity of PHE-Q-1 in investigating the emotional component of human intelligence and its clinical utility concerning one's level of cognitive-emotional dissonance and PHEM-2, during psychotherapeutic encounters conducted according to the brief or otherwise integrated strategic approach, is confirmed.